PP.31.21: BLOOD PRESSURE PATTERN IN PATIENTS WITH ACUTE HEART FAILURE. (June 2015) - Guberna, S.; Avram, N.; Raileanu, M.; Sinescu, C.
Abstract : Objective: The purpose of our study was to analise the blood pressure (BP) profile in patients with acute pulmonary edema (APE)/ acute heart failure (AHF). Design and method: We analised 2 groups of 50 patients. The first group included patients hospitalized for APE/AHF symptoms and BP > 180 mmhg. The second group included patients who attended the Ambulatory for uncontrolled BP values (>180 mmHg) without APE or AHF symptoms. We excluded patients with mitral or aortic valvular disease, systolic dysfunction, elevated troponin level and those with bradycardia/ tachycardia. Each patient was subjected to ABPM after remission of acute symptoms. BP was measured every 15 min in the day and every 30 min in the night. Parameters followed: age, sex, dipper/nondipper profile, maximum systolic BP (SBP), maximum diastolic BP (DBP), the difference between maximum SBP and minimum SBP, the difference between maximum DBP and minimum DBP, % of BP values > 160/90 mmHg, diabetic status, diastolic dysfunction. Results: Patients with APE/AHF symptoms were older (the mean age was 70, 44 years in patients with APE and 59, 52 years in patients without APE). 66% of patients with APE had non dipper blood pressure profile and were more frequently women (68%) and 50% had type 2 DM. Maxiumum SBP was higher in patients with APE (the mean of SBP was 190, 6 mmHg vs 179, 6 mmHg in patients without APE) and the percent of BP > 160/90 mmHg was greater in this group (70, 4%, p = 0.00001). SBP variability- difference between maximum and minimum SBP was smaller in patient with APE (66.7% of patients with APE compared to 33.3% of patients without APE, p = 0.0003). DBP variability was smaller in patient with APE (73.2% of patients with APE, p = 0.0001) All patients with APE had or impaired relaxation or pseudonormalized pattern. 50% of patients with AHF were diabetics, 42% of patients had impaired glucose tolerance. Conclusions: Patients with APE/AHF symptoms were more frequently diabetics with impaired relaxation or pseudonormalized pattern, had higher SBP and DBP and the variability of SBP/DBP was smaller. Also patients with APE/AHF had non dipper profile.